STRATEGI GURU DALAM MENGATASI KESULITAN BELAJAR MATEMATIKA PADA SISWA KELAS IV SD NEGERI SAMAHANI - Fadhillah; Nisrina; Jatu Wahyu Wicaksono (Jurnal Pendidikan Dasar, 2022)
fields of science. There are students who can take their learning activities smoothly without experiencing difficulties, but on the other hand not a few students who actually learn to experience various difficulties. In particular, this study aims to describe the teacher's strategy in overcoming the difficulty of learning mathematics in students of grade IV of Samahani State Elementary School. The approach that will be used in this study is a qualitative approach with a descriptive type. The subjects in this study were grade IV teachers and 9 students of grade IV Samahani State Elementary School. Data collection techniques through observation, interviews, questionnaires and documentation. Data is analyzed using data reduction, data presentation, and conclusion withdrawal. Based on the research that has been carried out, it can be concluded that the factors that cause the onset of difficulty learning mathematics in students come from internal factors and external factors. (1) Internal factors of students, namely, things or circumstances that come from within the student himself include (a) the low intellectual / intellectual intelligence of the student. The strategy carried out by teachers in overcoming the difficulty of learning mathematics is by knowing or recognizing the weaknesses of students in the math material. (b) the unstable emotions and attitudes. The strategy carried out by teachers in overcoming the difficulty of learning mathematics is to encourage and motivate students who have difficulty in learning mathematics. (2) External factors of the student include all situations of the surrounding environment conditions that do not support the student's learning activities. (a) Family environment, the strategy carried out by teachers in overcoming math learning difficulties is to inform about the advantages and disadvantages of students, so that teachers can find solutions together with parents about what teachers can do at school and parents at home. (b) The community environment. The strategy carried out by teachers in overcoming math learning difficulties is to use learning media such as audio visual media, and (c) The school environment. The strategy carried out by teachers in overcoming the difficulty of learning mathematics is by providing tasks / exercises.